Kebijakan Kurikulum dalam Pembelajaran Bahasa Arab - S. Inaku, Miskat; Laubaha, Wiya (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2022)
This research seeks to explore the theoretically and practically in understanding Arabic language learning curriculum policies that have existed in Indonesia since the beginning, namely the 1947 curriculum until now the 2013 curriculum (KMA 184). The existence of a curriculum policy (KMA 184) is due to internal challenges, namely learning Arabic in madrasas still tends to be structuralistic, less functional and less communicative. The external challenge is that the tendency of Arabic with the fushha (standard) pattern has shifted to the amiyah (market language) pattern. The Ministry of Religion establishes learning Arabic as a compulsory subject from the madrasah ibtidaiyah level to tertiary institutions at all educational institutions under its auspices. The curriculum changes and improvements are in order to develop the ability to communicate in Arabic, both spoken and written which includes four language skills namely, listening (Istima'), Speaking (Kalam), Reading (Qiraat), and writing (Kitabah) and is expected to be able to improve the quality of human resources. The type of research used is qualitative research whose data are presented descriptively. Based on the object, this research is library research. The data are collected by citing, then concluding, so that the result of this research is that curriculum policy in learning Arabic in Indonesia is carried out in a balanced and proportional manner, this can be seen in using the approach and models in each phase of curriculum change.